Mitigating the past: Landscapes and memory fabrications in Cape Verde - Sarmento, João Carlos Vicente (2011)
This chapter attempts to explore the construction of landscape and memory in Cape Verde. It deals with the different ways in which three sites in the island of Santiago – an Old Fort and a Historical Town; a Concentration Camp; and a Global Resort – participate in the erasure, maintenance and creation of memory, forging new ways of collective identity. All three sites are embedded in local as well as global forces and spatial processes, and encapsulate the complexity of memory making. Through the analysis of the changes taking place on-site, I attempt to unravel the processes and outcomes of the construction of memory which are perceptible on the island’s landscapes. The ways in which they are being constructed, re-constructed, invented, forged and embedded in space are the means to explore identity in this Atlantic nation-state archipelago.